Nutritional Knowledge Levels of E-sports Players - Deniz Arlı; Serdal Öğüt; Ayçıl Özturan Şirin (Turkish Journal of Health Science and Life, 2026)
Background: E-sport is a novel sport type that e-athletes can have a sedentary lifestyle which causes various health problems, such as obesity. Objective: This study aimed to determine the level of nutritional knowledge of e-sports players. Methods: The data was collected and evaluated using a personal data form and the Nutrition for Sport Knowledge Questionnaire (NSKQ). Results: A total of 90 e-sports players participated in the research. All participants were male and the average age was determined to be 21.8±2.11. It was found that 98.9% of the participants had poor nutrition knowledge, while only 1.1% had average-level knowledge. The average score of the e-sports players on the NSKQ was 24.88±1.00. The BMI values of the e-sports players were determined to be an average of 25.56 ± 0.8 kg/m2. No significant relationship was found between the e-sports players' nutrition knowledge levels and league status (p>0.05). Conclusion: Based on these data, the nutrition knowledge level of e-sports players is weak, and their BMI values indicate that they are overweight. To support health and optimize nutrition-related knowledge among e-sports players, nutrition education programs may be beneficial.